EFEKTIVITAS PELAYANAN ADMINISTRASI TERPADU KECAMATAN DI KECAMATAN NGAMPRAH KABUPATEN BANDUNG BARAT - Anisa Fitri Amalia (Jurnal Caraka Prabu, 2018)
The title of this research is "The Effectiveness of Integrated District Administration Services in Ngamprah District, West Bandung Regency". The problem in this research is that the implementation of Integrated District Administration Services is not optimal which causes the implementation of these services to be less than optimal. The research method that researchers use is descriptive research methods with a qualitative approach. The technique of determining the informants used was purposive sampling technique. The results showed that the implementation of Integrated District Administration Services was still not optimal, this can be seen from: (1) inaccurate service time, (2) inadequate number of human resources, (3) mismatch of service mechanisms in licensing services, (4) lack of availability and maintenance of facilities and infrastructure, (5) lack of socialization and provision of information by the Ngamprah District Government, (6) the community's participation in providing evaluation is not maximal.